The reception of French painting in Britain, c. 1690–c. 1740 - Lee-Woolfe, Tamsin (2018)
The reception of French pictures, artists and art literature in Britain during the early eighteenth century has hitherto remained an understudied area within British art history. Modern scholarship has often characterised this period as experiencing an influx of continental influences which aided the development of British art, collecting, and patronage. However, there is the tendency to focus such a study within the latter decades of the century. This thesis combines document-based research with pictorial study in order to determine the ways that English audiences responded to the presence of French pictures, but also imitated, modified and criticised French artistic ideas and forms during the period